Peran Sultan Alp Arselan Dalam Mengembangkan Dinasti Saljuk (1063-1072 M) - Siti Chotijah (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study examines the history of the Seljuk Dynasty and Sultan Alp Arselan in the process of development of the Seljuk Dynasty. The purpose of this study is to reveal the role of Sultan Alp Arselan in the development of the Seljuk Dynasty. This study uses historical research methods which include heuristic, verification, interpretation and. This study is developed from the perspective of political theory and approach. Part of the theory was used to determine the role played by Sultan Alp Arselan through a number of decisions and actions. A political approach is used to determine the background and considerations of Sultan Alp Arselan policy decisions. Result: 1) The Seljuk dynasty was founded by Sultan Tughrul Bek in 1037 and from 1055 the Seljuk dynasty played an active part in the Abbasid Dynasty. Sultan Alp Arselan became the second sultan of the Seljuk dynasty after Sultan Tughurul Beg. Khurasan born in 1029, became a military leader and ascended the Sultans throne. He is known as a strong beautiful generous compassionate and positive leader. 2) Sultan Alp Arselans attempts to advance his dynasty included taking control of the territorys administrative system expanding state conditions and allowing the establishment of the Nizamiya Seminary.